Bifurcations of phase portraits and exact solutions of the (2+1)-dimensional integro-differential Jaulent-Miodek equation - Ali, Karmina K.; Tarla, Sibel (Springer, 2024)
This paper is dedicated to exterminate the (2 + 1)-dimensional integro-differential Jaulent-Miodek equation, a prominent model linked to energy-dependent Schr & ouml;dinger potential. This equation is employed in a wide array of disciplines, including fluid dynamics, condensed matter physics, optics, and various engineering systems. First, we are given to derive exact wave solutions for the (2 + 1)-dimensional integro-differential Jaulent-Miodek equation using an innovative approach known as the new modified unified auxiliary equation method. We offer a comprehensive visual representation and some exact solutions propagate of these solutions in 2D and 3D plots, using various parametric values for a comprehensive analysis. In addition, we employed the planar dynamical system method to study phase portraits and chaotic behavior of the governing equation. Through the analysis of phase portraits, the sensitivity of dynamic system is examined. The chaotic behavior of dynamic system is examined by time series, Poincar & eacute; section, and 2D, 3D phase portraits.
Keywords: The (2+1)-dimensional integro-differential; Bifurcation theory; A new modified unified auxiliary equation method; Exact solutions